Mechanistic insights on immobilization and decontamination of hexavalent chromium onto nano MgS/FeS doped cellulose nanofibres. (August 2019) - Sankararamakrishnan, Nalini; Shankhwar, Anil; Chauhan, Divya
Abstract: Sustainable bio nano composite comprising of nanoMgS/FeS doped cellulose nanofibres (FeMgSCNF) was prepared, characterized by various techniques and assessed for the decontamination of Cr(VI). Cellulose nanofibres (CNF) acts as a template and stabilizer and prevents agglomeration of FeS/MgS nano particles. MgS present in the nano-composite provides a barrier to suppress aerial oxidation of Fe(II) and provided additional source of sulfide ions. An adsorption capacity in the order of 142.8 mg/g of the bionano composite was exhibited towards hexavalent chromium. Both FeSCNF and FeMgSCNF followed pseudo first order and pseudo second order kinetics with regression coefficients >0.96. X-ray photoelectron spectroscopy (XPS) studies indicated that decontamination of Cr(VI) follows the route of electrostatic attraction, ion-exchange followed by reduction of Cr(VI) to Cr(III) and immobilization of Cr(III) as chromic oxide and Fe-Cr mixed oxide. Toxicity characteristics leaching tests revealed the efficacy of immobilization. Finally the developed sorbents were successfully applied to the removal of chromium from tannery waste effluents. Graphical abstract: Image 1 Highlights: Novel FeS and MgS doped cellulose nanofibres (CNF) were prepared for the first time. MgS acts as a barrier to suppress aerial oxidation of Fe(II). CNF prevents agglomeration of FeS. FeMgSCNF exhibited very high adsorption capacity for Cr(VI). XPS Studies revealed complete decontamination of Cr(VI) to Cr(III) by FeMgSCNF.